Monkeys, Wasps and Gods: Graphic perspectives on Middle Horizon and later pre-Hispanic painted funerary textiles from the Peruvian coast - Dimitri Karadimas (Nuevo mundo - Mundos Nuevos, 2016)
This paper examines the iconography of a group of pre-Columbian Andean woven textiles that, under the cloak of apparent heterogeneity, often hides a common thematic structure. It was widespread among pre-Columbian societies of the coast to individualise their art by applying thematic variations to the images they painted on cotton textiles: graphic compositions of a standing figure surrounded by a symmetrical arrangement of monkeys, felines and birds. Used as funerary shrouds to enclose the corpse after death, the woven textiles and their iconography performed the transformation of the recently deceased person into his new afterlife entity.The presupposition of our presentation is that the painted scenes were inspired by mythological references. They present a journey that the deceased must undertake to achieve immortality. Others have already completed the journey and, as major mythological heroes, they are still visible as celestial bodies, having triumphed in their battle against the stars for immortality. Their alternate diurnal and nocturnal presence can still be seen today.By carrying out an iconographical analysis based on contemporary Lowland mythology gathered in Colombia, in which this celestial antagonism is presented, we propose to find the homogeneity in these variations. Our aim is to bring new light to the reason for their presence as images on the mortuary materials of pre-Hispanic coastal societies.